1995
DOI: 10.1016/0006-3207(94)00121-6
|View full text |Cite
|
Sign up to set email alerts
|

The conservation of arboreal marsupials in the montane ash forests of the central highlands of Victoria, south-eastern Australia — VII. Modelling the persistence of Leadbeater's possum in response to modified timber harvesting practices

Abstract: A computer model for Population Viability Analysis (PVA) was used to simulate the relationship between the persistence of populations of the endangered species, Leadbeater's possum, Gymnobelideus leadbeateri and the implementation of a range of possible modified timber harvesting practices in two wood production blocks within the montane ash forests of the central highlands of Victoria, south-eastern Australia. The results of our analyses revealed that under the existing conservation strategies there was a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Nonetheless, it has been found that survival of species is related to several landscape and habitat variables such as the extent and quality of habitat (Lovejoy et al, 1986;Laurance, 1994;Lindenmayer and Possingham, 1995), connectivity between fragments (Lovejoy et al, 1986;Laurance, 1994;Lindenmayer et al, 1994), time since isolation and elevation (Lindenmayer et al, 1994), distance to the nearest fragment (Fitzgibbon, 1997) and location of the fragment in the landscape (Laurance 1990;Lindenmayer and Possingham, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it has been found that survival of species is related to several landscape and habitat variables such as the extent and quality of habitat (Lovejoy et al, 1986;Laurance, 1994;Lindenmayer and Possingham, 1995), connectivity between fragments (Lovejoy et al, 1986;Laurance, 1994;Lindenmayer et al, 1994), time since isolation and elevation (Lindenmayer et al, 1994), distance to the nearest fragment (Fitzgibbon, 1997) and location of the fragment in the landscape (Laurance 1990;Lindenmayer and Possingham, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These behaviours make bats particularly vulnerable to reduction in abundance and quality of roosting habitat. Forests that are managed for timber production do not have as many cavity-bearing trees as unmodified forests (Mackowski 1984;Newton 1994;Lindenmayer & Possingham 1995). Therefore, it can be assumed that logging will reduce both abundance of cavities, and range of cavity sizes and quality.…”
Section: Roosts Selection and Implications For Conservationmentioning
confidence: 99%
“…Stochastic methods of fire scenario development such as those used by Lindenmayer and Possingham (1995) may be useful as scientific model inputs but their reliance on random factors limits their utility as management planning tools. To provide an objective means of rating a road or road system it is then necessary to develop repeatable 'reference' fire conditions that road options may be judged against.…”
Section: Location and Site Descriptionmentioning
confidence: 99%